Amending power under the Indian Constitution - Keshavamurthy, C.V. (New Delhi, 1982)
The Indian Constitution underwent its first surgery in its neo-natal period itself with the first amendment passed in 1951. Eversince there has been a continuing conflict of opinion between Jurists and Judges on the one side and Political Leadership on the other regarding the scope of the Amending Power that is available under the provisions of the Indian Constitution. In the strong challenges that were levelled against the pretention of Parliament to the plenitude of amendatory powers, judicial opinion has swung from permission to prohibition. The reasons may not be far to seek. When Shankari Prasad acknowledged Parliament's competence to amend the Constitution a plethora of them prompted the judicial reaction in Golaknath. As expected Parlia ment responded with an assertion to unlimited powers of amendment to which the highest court found limitations in terms of what is now familiarly known as 'The Basic Structure Theory'.
Keywords: Constitutional amendments India